Redescription of Astyanax multidens eigenmann, 1908 (Characiformes: Characidae), a small characid of the Brazilian Amazon - Marinho, Manoela M. F. [UNESP]; Birindelli, José L. O. (FapUNIFESP (SciELO), 2013)
Astyanax multidens is redescribed based on syntypes and additional specimens from the rio Amazonas at Silves, Amazonas State and Óbidos, Pará State, and the rios Trombetas, Tapajós, Xingú, and Araguaia. Astyanax multidens is distinguished from congeners by the unique combination of five to seven maxillary teeth, 31 to 34 pored lateral-line scales, 20 to 23 branched analfin rays, and a dark triangular blotch restricted to the middle caudal-fin rays. Astyanax multidens was collected syntopically with Jupiaba paranatinga in the rio Tapajós basin and with Jupiaba cf. essequibensis in the rio Xingu basin, which have paired anteriorly oriented pelvic-fin spines, a antipredatory mechanism. Based on the external morphological similarity between Astyanax multidens and the two species of Jupiaba, their sympatric occurrence, and their distinct phylogenetic position, we interpret this a case of Batesian mimicry. © 2013 Sociedade Brasileira de Ictiologia.
Keywords: Jupiaba; Mimicry; Neotropical; Taxonomy